SWITCH II: Phase III randomized, sequential, open-label study to evaluate the efficacy and safety of sorafenib-pazopanib versus pazopanib-sorafenib in the treatment of advanced or metastatic renal cell carcinoma (AUO AN 33/11) - Retz, Margitta; Teber, Dogu (European journal of cancer, 2019)
Purpose - This trial compared the sequential therapy with the multikinase inhibitor sorafenib (So) followed by pazopanib (Pa) or vice versa in advanced/metastatic renal cell carcinoma (mRCC) patients. - Methods - This multicenter, randomized phase 3 study assessed the sequential use of So-Pa versus Pa-So in patients with mRCC without prior systemic therapy. Pts were randomized to So 2 × 400 mg/day followed by Pa 1 × 800 mg/day in case of progression or intolerable toxicity or vice versa. Primary endpoint was total PFS (tPFS), defined as time from randomization to progression, or death during second-line therapy. Key secondary endpoints included overall survival (OS), first-line PFS, disease control rate (DCR) and safety. - Results - A total of 377 pts were randomized (So-Pa, n = 189; Pa-So, n = 188). Recruitment of a total 544 pts was calculated, but actual accrual rate turned out to be lower than expected. The primary endpoint median tPFS was 8.6 mo (95% CI 7.7-10.2) for So-Pa and 12.9 mo (95% CI 10.8-15.2) for Pa-So with a hazard ratio (HR) of 1.36 (upper limit of one-sided 95% CI 1.68), which exceeded a predefined HR <1.225 as a one-sided 95% confidence interval. Non-inferiority of So-Pa regarding tPFS was not met. Secondary endpoints displayed marked statistical differences in favor of Pa-So in first-line PFS and DCR but not for OS and 2nd-line PFS. Side effect profiles were consistent with known toxicities of the respective multikinase-inhibitor including diarrhea, fatigue, hand-foot skin reaction and hypertension. - Conclusions - Non-inferiority of the primary endpoint tPFS could not be demonstrated for So-Pa. The results for first-line PFS and DCR favored the Pa-So sequence. - Trial registration - NCT01613846, www.clinicaltrials.gov.